Journey to Shariah Hospital: An Indonesian Experience - Aisyah Ismail, S; Hamid, B; Sulistiadi, W; ., Sagiran (KnE Life Sciences, 2018)
Introduction and Purpose. As the world’s most populous Muslim country, Indonesia carries the responsibility to establish an Islamic healthcare system that is of superior quality. Believing that Islamic Shariah is the best system for any activity, the need to translate the system into a measurable and objective healthcare quality tool is eminent. In 2015, the Standard of Shariah Hospital Certification was published, and in 2016, the National Shariah Council produced a fatwa on the implementation of Shariah Hospital. In 2017, a second version of the Standard was published to be formalized by the National Shariah Council as the awarding body. Approach and Value. The concept uses the maqasidic approach in its structure and refers to the National Hospital Accreditation Commission format. Normative standards are conserved and Shariah values are added in all critical points. Further technical details are produced to ensure proper implementation of the standards, which are divided into Shariah management and Shariah services. Two hospitals were appointed as the pilot project and many more are awaiting its implementation. Keywords: Shariah-compliant hospital, Shariah Hospital Certification, service quality improvement, Shariah hospital standards